PENGARUH PENAMBAHAN TEPUNG AMPAS TAHUTERHADAP NILAI GIZI DAN MUTU ORGANOLEPTIK GEBLEK - Santoso, Hadi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
The aim of this study was to determine the effect of adding flour of tofu solid waste to nutritional value and organoleptic quality of geblek. The study used a complete randomized design with three replications. The factors studied were the concentration of the addition of flour of tofu solid waste with variations 0%, 2%, 4% and 6%. The parameters observed were moisture content, protein content, fat content, carbohydrate content, phytic acid content, crude fibber content and organoleptic quality of raw and cooked geblek. The results showed that the addition of flour of tofu solid waste will affect the nutritional content of geblek, especially its protein content. Addition of flour of tofu solid waste did not significantly influence phytic acid content in cooked geblek while in raw geblek, increased phytic acid significantly occurred in addition of 6% flour of tofu solid waste. Based on the organoleptic test, the panellists favoured raw and cooked geblek with the addition of 2% flour of tofu solid waste whereas raw geblek had water content of 46.59 0.32%, ash content 0.59 0.06%, protein content 0.61 0,00%, carbohydrate content 52,21 0,26%, and phytic acid content 0,009 0,00% while cooked geblek have moisture content 27,20 1,41%, ash content 1,59 0,06 %, protein content 0,72 0,00%, fat content 10,42 0,05%, carbohydrate content 60,08 1,42%, crude fibber content 0,93 0,12%, and phytic acid content 0.018 0.01%.